Harmonization and integration of water saving options in Lebanon - Karaa K.; Karam F.; Tarabey N. (Harmonization and integration of water saving options. Convention and promotion of water saving policies and guidelines, 2007)
In 2020, the water balance in Lebanon could be negative if concern entities in water management do not apply the water saving options. Ministry of Energy and water is the responsible of water policy and Water Authorities are the responsible for execution of his master plan. At the end users level in agriculture sector, the Ministry of Agriculture has the responsibility on farm level. The absence of Water User Associations and extension in water management, bad maintenance and water pollution are the major causes of water looses. Legislation, law enforcement, research and education center activation, tariff policy, stakeholder's capacity building are the main factors for water management enhancement. The creation of the High Council for water is a major step on coordination of decision maker's activities, sharing knowledge and exchange of experience. His role will be decisive on updating and adjustment of Water National Master Plan.
5. WASAMED (WAter SAving in MEDiterranean agriculture) Workshop, 2006/05/03-07, Malta (Malta)